Passionate embrace: Luther on love, body, and sensual presence - Gerle, Elisabeth (Cascade Books, 2017)
"Luther, passion, and sensualism? In an age of body worship as well as body loathing, Elisabeth Gerle explores new paths. Protestant ethics has often been associated with work and duty, excluding sensuality, sexuality, and other pleasures. Gerle embarks on a conversation with Martin Luther in dialogue with contemporary theologians on attitudes toward body, sensuality, desire, sexuality, life, and politics. She draws on Eros theology to challenge traditional Lutheran stereotypes, such as the dichotomies between different forms of love, as well as between spirit and body. Gerle argues that Luther's spiritual breakthrough, where grace and gifts of creation became central, provides new meaning to sex and desire as well as to work, body, and ordinary life. Women are seen in new light--as companions, autonomous ethical agents, part of the priesthood of all. This had revolutionary consequences in medieval Europe, and it represents a challenge to contemporary theologies with a nostalgic appetite for austerity, asceticism, and female submission. Luther's erotic and gender-fluid language is a healthy challenge to oppressive political structures centered on greed, profit, and competition. A revised Scandinavian creation theology and a deep sense of the incarnational mystery are resources for contemporary theology and ethics." --